1997
DOI: 10.1089/lap.1997.7.87
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Intraperitoneally Retained Gallstones with Different Morphologic and Microbiologic Characteristics: An Experimental Study

Abstract: Management of intraperitoneally retained gallstones after laparoscopic cholecystectomy (LC) is controversial, as their natural course is not known. This study was undertaken to assess the probable effects of stone morphology and clinically obvious infection on the outcome of retained gallstones in a mouse model. Forty albino mice were divided into four groups. Group I served as the control group (simple laparotomy, n = 10). Groups II, III, and IV (n = 10 in each group) were study groups. "Intact-sterile-choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The inflammatory response is greater in the presence of infection [2,57], stone fragmentation [57], and with pigmented stones [18,20]. Pigment stones are more likely to be infected than cholesterol stones.…”
Section: The Natural History Of Peritoneal Gallstonesmentioning
confidence: 99%
“…The inflammatory response is greater in the presence of infection [2,57], stone fragmentation [57], and with pigmented stones [18,20]. Pigment stones are more likely to be infected than cholesterol stones.…”
Section: The Natural History Of Peritoneal Gallstonesmentioning
confidence: 99%
“…As shown in several studies, [2][3][4][5][6][7] whether the bile is infected or not, bile and gallstones are at an increased risk for abscess formation and formation of adhesions. The type of stones is one of the factors involved in complication occurrence; more experimental studies and reported cases show that the bacterial contamination is less in cholesterol calculi than in pigment stones (Black, brown or mixed).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] During laparoscopy, the incidence of gallbladder perforation is 13 to 40%, 21 with a mean of 18. 3%out of those 8 studies with more than 500 LCs.…”
Section: Management Of Gallbladder Perforationmentioning
confidence: 99%
“…The experience of the surgeon and the difficulty of the operation (acute or chronic cholecystitis and adhesions in the right upper quadrant) are considered significant risk factors for gallbladder perforation during LC [6,8,16,17]. Inflammation in response to peritoneal gallstones is increased in the presence of infection, stone fragmentation, and pigmented stones [7,20].…”
Section: Discussionmentioning
confidence: 99%